Dampak Pengembangan Pariwisata Terhadap Pendapatan Asli Daerah (PAD) Di Kabupaten Lombok Tengah, Nusa Tenggara Barat Tahun 2002-2016 - Rois, Ihsan; Fadliyanti, Lukuk; Wijimulawiani, Bq.Saripta (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
This study aims to analyze the impact of tourism development on regional original income in the district of Central Lombok. The data used in this study is time series data for the period of 2002-2016 obtained from Region Income Broad, Tourism and Culture Broad, and Statistic Broad of the Lombok Cental Region. The variables used in this study are the number of tourists, the number of hotels and restaurants, the number of attractions against and the average length of stay of region income in the district of Central Lombok. Analyzer used multiple regression analysis using Ordinary Least Square (OLS) method.